Age impacts left atrial functional remodeling in athletes. - Cynthia Cousergue; Eric Saloux; Emmanuel Reboursière; Amélia Rocamora; Paul Milliez; Hervé Normand; Amir Hodzic (PLoS ONE, 2022)
Aim Age-associated changes in cardiac filling and function are well known in the general population. Yet, the effect of aging on left atrial (LA) function, and its interaction with left ventricular (LV) adaptation, remain less described when combined with high-intensity chronic training. We aimed to analyze the effects of aging on LA and LV functions in trained athletes. Methods and results Ninety-five healthy highly-trained athletes referred for resting echocardiography were included. Two groups of athletes were retrospectively defined based on age: young athletes aged <35 years (n = 54), and master athletes aged ≥35 years (n = 41). All subjects were questioned about their sports practice. Echocardiographic analysis of LV systolic and diastolic functions (2D-echo, 3D-echo, and Doppler), as well as LA 2D dimensions and phasic deformations assessed by speckle tracking, were analyzed. Master athletes (mean age = 46.3 ± 8.3 years, mean duration of sustained training = 13.7 ± 8.9 years) exhibited significantly stiffer LV and LA with reduced LV early diastolic functional parameters (ratio E/A, peak e', and ratio e'/a'), LA reservoir and conduit strain, whereas LA volume, LA contractile strain and LV peak a' were higher, compared to young athletes. Multivariate regression analysis confirmed that age was predictive of peak e', LA reservoir strain and LA conduit strain, independently of training variables. LA phasic strains were strongly associated with LV diastolic function. Conclusions Regardless of chronic sports practice, master athletes exhibited age-related changes in LA function closely coupled to LV diastolic properties, which led to LV filling shifts to late diastole.